Visualisasi Nilai-Nilai Insight Unlimited Melalui Eksplorasi Teknik Crochet Dalam Window Display - Sharlene Louis (Penerbit dan Percetakan, CV. Picmotiv, 2025)
This study investigates the use of Crochet fiber art in window display s as a medium for visual storytelling and spiritual expression, analyzed through Roland Barthes’ semiotics. Focusing on Insight Unlimited’s retail installation, it explores how handmade textures act as signifiers that convey deeper meanings of community, faith, and sustainability. Using qualitative methods including expert interviews, case studies such as Hermès displays, and material experiments with bobble stitches and yarn painting the research reveals how crochet’s tactile nature naturalizes ideological messages, aligning with Barthes’ concept of myth. Viewers often interpret these displays beyond commercial intent, perceiving them as critiques of fast fashion or as spiritual reflections. The final 2m × 1m display at Kota Kasablanka Mall exemplifies how craft can challenge the norms of visual merchandising. The study contributes to semiotic analysis in retail design, integrates faith-driven design approaches, and highlights slow fashion aesthetics in commercial environments.